2023
DOI: 10.3390/bioengineering10040406
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Bio-Signals Using Block-Based Haar Wavelet Transform and COVIDOA for IoMT Systems

Abstract: Background: Bio-signals are the essential data that smart healthcare systems require for diagnosing and treating common diseases. However, the amount of these signals that need to be processed and analyzed by healthcare systems is huge. Dealing with such a vast amount of data presents difficulties, such as the need for high storage and transmission capabilities. In addition, retaining the most useful clinical information in the input signal is essential while applying compression. Methods: This paper proposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…One important issue when compressing the FPCG signal is that no signal degradation occurs; perhaps the matter's importance is because the signal's form carries vital information in diagnosing any problems in the heart. Generally, [16,17,18,19] and Block-Based Haar Wavelet Transform and COVIDOA [20] are commonly used signal compression techniques.…”
Section: Introductionmentioning
confidence: 99%
“…One important issue when compressing the FPCG signal is that no signal degradation occurs; perhaps the matter's importance is because the signal's form carries vital information in diagnosing any problems in the heart. Generally, [16,17,18,19] and Block-Based Haar Wavelet Transform and COVIDOA [20] are commonly used signal compression techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In [14], the authors suggested a compression technique for bio-signals well-suited to IoMT use. This approach uses block-based HWT to isolate features from the input signal and then uses the innovative COVIDOA to choose the most significant characteristics for reconstruction.…”
mentioning
confidence: 99%